Intelligent agents for an Internet-based global crisis communication system - Goh, Ong Sing; Fung, C.C.; Lee, M.P. (Universiti Teknikal Malaysia Melaka, 2005)
In times of crisis, an effective communication mechanism is paramount in providing accurate and timely information to the community. Recent examples are the outbreak of SARS, bird flu, mad cow diseases, September 11 attacks and the 2004 tsunamis. Such events have illustrated the importance of an effective and efficient crisis communication system. In this paper, it is proposed the incorporation of an intelligent agent software robot into a crisis communication portal (CCNet) in order to send alert news to subscribed users via email and others mobile services such as Short Message Service (SMS), Multimedia Messaging Service (MMS) and General Packet Radio Services (GPRS). The proposed system consists of the integration of an intelligent conversation agent that is employed to gain trust from the users of the portal and an Automated Knowledge Extraction Agent (AKEA), which retrieves first hand information from relevant sources such as WHO.org, CBC Canada, info.gov.hk and Sars.gov.sg.